Health Awareness in Kindergarten Teachers (Journal of the College of Basic Education, 2020)
The issue of health awareness is one of the main issues that require attention from researchers because it is important in the dissemination of information related to the health of individuals and to preserve their lives and avoid diseases that may affect them as a result of changing lifestyle and the emergence of new diseases constantly. The purpose of this research is to identify the level of health awareness of kindergarten teachers and the extent of differences in this awareness according to the specialization of the nanny (kindergartens, non-kindergartens) and the years of service (less than 5 years, 5 years and more) In the Directorate of Education of the second Rusafa in the province of Baghdad in the state kindergartens. A random sample of (150) nannies distributed to (10) government kindergartens was selected. To achieve the research objectives, an objective measure of health awareness was developed in the nannies, which resulted in discrimination, honesty and persistence. Using a range of statistical means. The results reached the owners of nannies with a high degree of health awareness, and showed no differences in health awareness according to the specialization of nannies. And the emergence of differences depending on the years of service in the kindergarten for the service (5) years and more. In the light of these results, the research produced a set of recommendations and proposals for future studies